2016
DOI: 10.1016/j.chb.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a web-based gambling intervention program for high school students: A preliminary randomized study

Abstract: . The efficacy of a web-based gambling intervention program for high school students: A preliminary randomized study. Computers in Human Behavior, 55, 946-954. AbstractEarly onset in adolescent gambling involvement can be a precipitator of later gambling problemsThe aim of the present study was to test the preliminary efficacy of a web-based gambling intervention program for students within a high school-based setting. Students attending a high school in Italy (N = 168) participated in the present study (58% m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 54 publications
(55 reference statements)
2
49
0
1
Order By: Relevance
“…The majority of studies noted significant improvements in problem gambling over time using a variety of measures. Of the seven randomized-controlled trial (RCT) design studies, five found significant improvement from the Internet based intervention group over controls (no treatment in all cases) [7] [7,9] [10] [16] [15]. In addition to problem gambling improvement (based on problem gambling scores),these studies also found improvements in gambling behaviours, anxiety, and depression [9].…”
Section: Principle Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of studies noted significant improvements in problem gambling over time using a variety of measures. Of the seven randomized-controlled trial (RCT) design studies, five found significant improvement from the Internet based intervention group over controls (no treatment in all cases) [7] [7,9] [10] [16] [15]. In addition to problem gambling improvement (based on problem gambling scores),these studies also found improvements in gambling behaviours, anxiety, and depression [9].…”
Section: Principle Findingsmentioning
confidence: 99%
“…Specific gambling related harms scales included the Problem Gambling Severity Index (PGSI) [6] [12] [22] [16] [23], Gambling Attitudes Scale (GAS) [7], South Oakes Gambling Screen (SOGS) [20], SOGS-R [19], and SOGS-RA [7], National Opinion Research Center DSM Screen for Gambling Problems (NODS) [8] [9] [11], Problem Gambling Significant Other Impact Scale (PG-SOIS) [13] and the Diagnostic and Statistical Manual for Mental Disorders criteria for pathological gambling (DSM IV) [6]. Of these scales the PGSI and the NODS were the most popular.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations